YAYASAN PEMBINAAN ANAK CACAT (YPAC) DI SURAKARTA SEBAGAI WADAH KEGIATAN PEMBINAAN YANG HUMANIS - Nindy Dyah Kusuma; Wiwik Setyaningsih; Hari Yuliarso (Universitas Sebelas Maret Surakarta, 2014)
Abstract : YPAC in Surakarta is a development and rehabilitation foundation of medical, education, social and skills rehabilitation for people with physical disabled type ( disability ) and multiple disabled type( mentally and physically ) . The foundation not only develops their talents and think abilities, but also has the ability to interact with human beings in it as well as humanistic environment. To realize YPAC which is humanist, design problems to be solved that ( 1 ) How to determine the required facilities disabled users in accordance with the specification requirements physically disabled , ( 2 ) How to determine the interior , exterior and landscaping of the building that can create an atmosphere that is friendly to the user universal and the environment in the process of rehabilitation and education . Through these problems, the design process is to apply the special needs of persons with disabilities within the city of Surakarta . Keywords: Humanits, YPAC, Physically Disabled.